Borges, Desire, and Sex - de la Fuente, Ariel (Liverpool University Press, 2018)
The Argentine Jorge Luis Borges, one of the most sophisticated writers of the twentieth century, suffered from sexual impotence. This emotionally overwhelming condition shaped his literary experience in ways that have not been understood. Until now Borges has largely been considered an asexual author who could not read, think, or write about desire and sex, but in this book historian Ariel de la Fuente shows that sexuality was a major preoccupation for him, both as a reader and as an author. De la Fuente has conducted an extensive literary investigation in Borges's figurative erotic library and presents for the first time a study of the relationship between Borges's sexual biography, his erotic readings, and the writing of desire and sex in his work. The author explores relevant literary questions while employing a historical method and the book is truly an interdisciplinary study at the intersection of history with Latin American, European, and Eastern literatures, poetry, philosophy, and sexuality. Argued with clarity, Borges, Desire, and Sex offers an unexpected perspective on the literature and figure of a world-wide influential author.